Trends and causes of maternal mortality in Jimma University Specialized Hospital, southwest Ethiopia: a matched case–control study - Legesse T; Abdulahi M; Dirar A (Dove Medical Press, 2017)
Tegene Legesse,1 Misra Abdulahi,2 Anteneh Dirar2 1Department of Public Health, Collage of Health Science, Mizan-Tepi University, Mizan Teferi, Ethiopia; 2Department of Population and Family Health, College of Health Sciences, Jimma University, Jimma, Oromia Regional State, Ethiopia Introduction: Measures of maternal death are fundamental to a country’s health and development status. In developing countries, it remains a daunting and largely unmet public health challenge. There were two studies completed over 10 years ago in Jimma University Specialized Hospital to identify trends, but recently there have been many changes in Ethiopia to reduce maternal death. Therefore, it is important to track the achievements made in Ethiopia in the context of Jimma University Specialized Hospital. No study undertaken in the country has quantified deaths of women from specific causes after controlling confounders.Objective: To assess trends and causes of maternal death in Jimma University Specialized Hospital, southwest Ethiopia.Methods: A time-matched case–control study was conducted on 600 (120 cases and 480 controls) females who utilized obstetrics and gynecology services from January 2010 to December 2014. To observe trends in maternal death, maternal mortality ratio was calculated for each year. Stata version 13 was used to analyze causal inference using propensity score matching method.Results: Maternal mortality ratio was 857/100,000 and had a decreasing trend from it’s highest in 2010 of 1,873/100,000 to it’s lowest of 350/100,000 in 2014. The leading cause of maternal death was hemorrhage (54%) (β=0.477, 95% confidence interval [CI]: 0.307, 0.647), followed by pregnancy-induced hypertension (20%) (β=0.232, 95% CI: 0.046, 0.419), and anemia (12%) (β=0.110, 95% CI: 0.017, 0.204).Conclusion: There is a decreasing trend of maternal death. Hemorrhage was the major cause of death identified in each year of study. Keywords: maternal death, maternal mortality, cause of maternal death and trend of maternal death